PENGEMBANGAN LKPD PADA BIDANG STUDI PENDIDIKAN AGAMA ISLAM DI SDN 02 SIKAPAK BARAT KOTA PARIAMAN - Putri Mardiah; Khairuddin , Khairuddin; Alimir, Alimir (CV. ADIBA AISHA AMIRA, 2024)
Islamic religious education is a planned conscious effort in preparing students to understand, recognize, live and believe in the teachings of the Islamic religion. The results of observations in the field are still not available student worksheets (LKPD) for students. This study aims to develop LKPD in the field of study of Islamic religious education at SDN 02 Attitudeak Barat, Pariaman City. This type of research is Research and Development (R&D) using the 4D model carried out up to the development stage (develop). The subjects of this study were Islamic Religious Education lecturers, PAI teachers and fourth grade students at SDN 02 Attitudeak Barat, Pariaman City. The research object is in the form of LKPD in the field of PAI studies on the Material of the Story of the Prophet Muhammad's Hijrah to the City of Medina for class IV SD/MI students. . Based on the results of the research conducted, it was found that teaching materials through validity tests obtained a validation value of 84.13% in the valid category and for the practicality test obtained a practicality value of 91.48% in the practical category through practicality tests by the teacher, very practical by students 91.22 % with very practical category. Therefore, it can be concluded that the development of worksheets in the field of Islamic religious education studies on environmental pollution material is valid and practical for use by fourth grade students.